Labourism and Economic Action: The Halifax Shipyards Strike of 1920 - Morton, Suzanne (Labour/Le Travailleur, 1988)
Abstract Post-war industrial action in Halifax culminated in the strike of the Marine Trades and Labor Federation against the Halifax Shipyards Limited. Increased strike activity was accompanied by and enhanced labour's formal political aspirations as expressed in the rejuvenation of the Halifax Labor Party. This article explores the economic and political events leading up to the summer of 1920 when the Halifax Shipyard Strike and a Nova Scotia Provincial election brought local events to a climax. Labourism, the broad political philosophy uniting labour activists in post-war Halifax, initially appeared to offer the ideal medium through which political and economic questions could be filtered and processed. But as labourites attempted to apply their philosophy to concrete situations, they exposed its inherent contradictions. The strike clarified their ideas while it revealed their weakness, and promoted the eventual fragmentation of the Halifax labour movement.